Qur’anic-based social and emotional learning (Q-SEL): An integrative model for internalizing Qur’an-based emotional spiritual quotient in modern education - Lucky, Widyani; Supandi, Supandi; Hanif Dzaky Turangan; Yuna Argadewi; Nardi, Nardi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2026)
Purpose - This study aims to formulate Qur’anic-Based Social and Emotional Learning (Q-SEL) as an integrative model for internalizing Emotional Spiritual Quotient (ESQ) based on the Qur’an in modern education. The study addresses the need to enrich Social and Emotional Learning with a Qur’anic spiritual dimension while maintaining its psychological and pedagogical foundations. Design/methods/approach - This study adopted an integrative literature review approach to examine and synthesize scholarly works related to Social-Emotional Learning (SEL), Emotional-Spiritual Quotient (ESQ), Islamic education, Qur’anic values, and character education. The literature was obtained from Google Scholar, Scopus, and ScienceDirect, covering publications from 2019 to 2025. A total of 35 relevant articles were reviewed and analyzed based on their relevance to the research focus, conceptual contribution, and methodological quality. The analysis was conducted thematically to identify key patterns, theoretical intersections, and potential frameworks for integrating social-emotional learning, spiritual intelligence, and Qur’anic values into character education. Findings - The findings show that Q-SEL consists of three main elements: Qur’anic values as the moral-spiritual foundation, ESQ as the internalization mechanism, and five SEL competencies as the operational learning structure. Qur’anic values such as iman, sabr, shukr, amanah, rahmah, ukhuwah, ta‘awun, justice, and ihsan strengthen self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. Research implication/limitation - This study is conceptual and literature-based; therefore, empirical testing is needed across educational levels and institutions. Originality/value - Q-SEL offers a conceptual contribution to Islamic education management by linking Qur’anic values, ESQ, and SEL for curriculum development, school culture, teacher development, and character education.